2007
DOI: 10.1186/1471-2105-8-153
|View full text |Cite
|
Sign up to set email alerts
|

How accurate and statistically robust are catalytic site predictions based on closeness centrality?

Abstract: BackgroundWe examine the accuracy of enzyme catalytic residue predictions from a network representation of protein structure. In this model, amino acid α-carbons specify vertices within a graph and edges connect vertices that are proximal in structure. Closeness centrality, which has shown promise in previous investigations, is used to identify important positions within the network. Closeness centrality, a global measure of network centrality, is calculated as the reciprocal of the average distance between ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 43 publications
3
70
1
Order By: Relevance
“…The distribution of the three centrality measures of all nucleotides in the 23S rRNA network (1JJ2) is presented in Figure 1. As previously observed in protein structures (17,26), the closeness parameter in the rRNA ribosome network showed a bell-shaped distribution (Figure 1A). Additionally, in accordance with previous observations in protein structures (19,25,54), the degree parameter of the rRNA structure follows a Poisson distribution (Figure 1C).…”
Section: Resultssupporting
confidence: 83%
“…The distribution of the three centrality measures of all nucleotides in the 23S rRNA network (1JJ2) is presented in Figure 1. As previously observed in protein structures (17,26), the closeness parameter in the rRNA ribosome network showed a bell-shaped distribution (Figure 1A). Additionally, in accordance with previous observations in protein structures (19,25,54), the degree parameter of the rRNA structure follows a Poisson distribution (Figure 1C).…”
Section: Resultssupporting
confidence: 83%
“…[44,45] Statistical analyses and network-based approaches have revealed a smallworld organization of protein topologies that emerged in studies of protein-folding mechanisms, [46][47][48] predictions of the binding-site residues, [49][50][51] analyses of functional and regulatory sites in protein networks, [52,53] and the prediction of catalytic clusters in enzymes. [51,54] Small-world allosteric networks and long-range communications in proteins appeared to be primarily governed by spatially separated clusters of specific functional residues. [55][56][57] These studies suggested that rapid transmission of allosteric interactions through small-world networks encoded in protein folds may have been a universal requirement encoded across diverse protein families.…”
Section: Structural and Network-based Models Of Allosteric Interactiomentioning
confidence: 99%
“…Centrality is reliable when it comes to predict critical residues (Chea & Livesay, 2007), but how can these be used to predict 3D structural and functional features? We have recently reported a tool named "JAMMING" to facilitate this task.…”
Section: Methods Based On Structural Informationmentioning
confidence: 99%